2016
DOI: 10.1111/jcmm.13031
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of systemic lupus erythematosus identified using mass spectrometry‐based proteomics: a systematic review

Abstract: Advances in mass spectrometry technologies have created new opportunities for discovering novel protein biomarkers in systemic lupus erythematosus (SLE). We performed a systematic review of published reports on proteomic biomarkers identified in SLE patients using mass spectrometry‐based proteomics and highlight their potential disease association and clinical utility. Two electronic databases, MEDLINE and EMBASE, were systematically searched up to July 2015. The methodological quality of studies included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 119 publications
1
30
0
2
Order By: Relevance
“…Interestingly, a previous study had shown low serum levels of clusterin in SLE patients, especially in those with proteinuria [81], suggesting it may be a more specific biomarker for LN. Furthermore, one of the highly specific peptides that distinguished LN from other types of CKD was a fragment of S100-A9, a finding consistent with the systematic review discussed above which identified S100-A9 as a promising SLE biomarker [65]. …”
Section: Novel Sle Testingsupporting
confidence: 69%
See 2 more Smart Citations
“…Interestingly, a previous study had shown low serum levels of clusterin in SLE patients, especially in those with proteinuria [81], suggesting it may be a more specific biomarker for LN. Furthermore, one of the highly specific peptides that distinguished LN from other types of CKD was a fragment of S100-A9, a finding consistent with the systematic review discussed above which identified S100-A9 as a promising SLE biomarker [65]. …”
Section: Novel Sle Testingsupporting
confidence: 69%
“…The complexity of these processes, as well as the highly dynamic changes that characterize them, have forced the development of highly advanced techniques for the study of more complete proteomes, as is the case of mass spectrometry (MS), and has shifted away from the use of electrophoresis to study individual proteins. The former technology allows for the identification and quantification of thousands of proteins in complex biological samples in a single run [65]. …”
Section: Novel Sle Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, developing useful strategies to predict and reduce drug–drug interactions is necessary to avoid drug‐induced side effects. Mass spectrometry utilized in biomarker discovery has become a powerful tool in the clinical area in recent years . Hence, developing a survey platform based on mass spectrometry is a good choice to identify the markers associated with drug–drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry utilized in biomarker discovery has become a powerful tool in the clinical area in recent years. [15][16][17][18][19] Hence, developing a survey platform based on mass spectrometry is a good choice to identify the markers associated with drug-drug interactions.…”
Section: Introductionmentioning
confidence: 99%